2016
DOI: 10.1007/s12031-016-0784-x
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation

Abstract: Mechanical trauma injury is a severe insult to neural cells. Subsequent secondary injury involves the release of inflammatory factors that have dramatic consequences for undamaged cells, leading to normal cell death after the initial injury. The present study investigated the capacity for arctigenin (ARC) to prevent secondary effects and evaluated the mechanism underlying the action of microRNA (miRNA)-199a and miRNA-16 in a mechanical trauma injury (MTI) model using SH-SY5Y cells in vitro. SH-SY5Y cells are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Next, we found that proliferation of the cultured NSCs in the BrdU incorporation assay almost exactly recapitulated the trend as MTT assay, in which 0.5 μM ARC displayed the highest promotional effect on proliferation of the cultured NSCs. These results demonstrated that ARC increased viability as well as proliferation ability of NSCs derived from mouse cochlear in a dose‐dependent manner, with the optimal dosage at 0.5 μM in our study (Figure d), consistent with reported effective concentration of ARC on other cell lines in previous studies (Song et al, ; Zhang et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Next, we found that proliferation of the cultured NSCs in the BrdU incorporation assay almost exactly recapitulated the trend as MTT assay, in which 0.5 μM ARC displayed the highest promotional effect on proliferation of the cultured NSCs. These results demonstrated that ARC increased viability as well as proliferation ability of NSCs derived from mouse cochlear in a dose‐dependent manner, with the optimal dosage at 0.5 μM in our study (Figure d), consistent with reported effective concentration of ARC on other cell lines in previous studies (Song et al, ; Zhang et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, ARC demonstrates neuroprotective effect on both primary neuron neurotoxicity, as well as memory and learning defects in mice induced by scopolamine with neural degenerative disease (Jang et al, ; Lee et al, ). In addition, ARC has also been reported to alleviate inflammation and confer neuroprotection against mechanical trauma injury in human neuroblastoma cells (Song et al, ), as well as in mouse primary neurons (Zhang et al, ). However, the effect of ARC in protecting against neuronal hearing loss has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…miR‐16 targets IκB kinase (IKK)‐α and IKKβ to inhibit expression of these 2 proteins and consequently blocks the activity of NF‐κB signaling pathway . miR‐21 targets proinflammatory genes’ mRNA to limit the activation of NF‐κB .…”
Section: Resultsmentioning
confidence: 99%
“…Then NF‐κB proteins are translocated from the cytoplasm into the nucleus to activate the target gene expression . Low‐intensity pulsed ultrasonography–stimulated BMDC exosomes were reported to contain high levels of miR‐16, which targeted IKKα and IKKβ, then enhanced their degradation . Thus, IκBα levels increased by miR‐16 sequestered more NF‐κB proteins in the cytoplasm and alleviated the activity of the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin is a major biologically active component of Arctium lappa L. ( A. lappa ), which is a popularly used vegetable as well as herbal medicine (Liu et al, ). Arctigenin exhibits distinct biological activities, including antiviral (Dias et al, ; Hayashi, Narutaki, Nagaoka, Hayashi, & Uesato, ), neuroprotection (Song et al, ; Zhu et al, ), antidiabetic (Huang et al, ; Zeng et al, ), and anticancer (Chen et al, ; Huang et al, ; Hsieh et al, ; Jeong, Hong, Jeong, & Koo, ; Lei, Gan, Zhao, Yu, & Hu, ; Li, Liang, Tian, & Hu, ; Maimaitili et al, ; Wang, Solorzano, et al, ; Susanti et al, ). A growing body of literature documents that arctigenin can induce cell cycle arrests, apoptosis, autophagy, and antimetastasis in multiple types of cancer cells, including prostate (Wang, Solorzano, et al, ), breast (Feng et al, ; Hsieh et al, ; Lou, Zhu, Zhao, Zhu, & Zhao, ; Maxwell, Lee, Kim, & Nam, ), lung (Lei et al, ), liver (Susanti et al, ), gastric (Jeong et al, ), ovarian (Huang et al, ), colon cancer (Li et al, ), and glioma (Maimaitili et al, ).…”
Section: Introductionmentioning
confidence: 99%